The Sapienza count-down for a healthy and sustainable diet - Donini, L. M.; Berry, E. M.; Pinto, A.; Giusti, A. M.; Muzzioli, L.; Lenzi, A.; Poggiogalle, E. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
The prevalence of obesity and of other non-communicable diseases related to overnutrition is significantly increasing in the past few years. Policy makers are called to counteract this  pandemic, orienting consumers towards a healthier and more sustainable diet.Most of the proposed initiatives are dedicated to the content of nutrients with “unfavourable” effects but, in fact, focusing the attention only or mainly on single foods or nutrients is not effective in decreasing the incidence/prevalence of non-communicable diseases. Whole dietary patterns play by far a more important role than specific dietary components in promoting health and modulating survival; and the adherence to eating patterns like the Mediterranean diet reduces the risk of non-communicable diseases. The challenge is therefore to be able to transmit information relating to a healthy eating pattern through positive messages in a few simple indications which in turn represent the nutritional, but also the sociocultural, environmental and economic characteristics of a healthy and sustainable dietary model.The Mediterranean Diet is normally proposed through a graphic depiction that represents a pyramid which is a simple and effective representation but not of immediate impact. For this reason, we are proposing to adopt the “Sapienza Count-down for a Healthy and Sustainable Diet” that will integrate the pyramid with a more immediate approach.